Discovering Teachers' Perceptions of Inclusive Teaching in Indonesia - Dyah Aniza Kismiati (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
Inclusive teaching is not something new in the world of Education. However, its emphasis in the Merdeka curriculum makes inclusive teaching steal the attention of many education observers. This study aims to determine the perception of teachers in Indonesia (elementary school teachers, junior high school teachers and senior high school teachers) on the importance of inclusive teaching in learning. This research is a survey study conducted on teachers in Indonesia, with random sampling. The sample number of teachers who were respondents was 46 teachers. To obtain data, researchers used an instrument in the form of a questionnaire in the form of a Likert scale with five scales and yes or no questions. As additional data, researchers conducted interviews conducted on several samples of teachers. The data obtained is then analyzed quantitatively and poured into tables and graphs. From the results of the analysis, it is known that teachers attach great importance to inclusive teaching. 82.61% teachers argue that inclusive teaching is a good idea. However, in reality, the application of inclusive teaching has not been optimal. One of the obstacles in optimizing the application of inclusive teaching is the selection of appropriate learning strategies in inclusion classes. This is what needs to be explored in order to find appropriate learning strategies for inclusion classes.